Mobil Listrik dan Solar Sell sebagai Alternatif Daya - Purbo Wartoyo, Bayu; Umboro Wahyu Nur Wening, Ida (Politeknik Penerbangan Makassar, 2021)
A solar cell or solar cell is a device or component that can convert sunlight energy into electrical energy using the principle of the photovoltaic effect. What is meant by the Photovoltaic Effect is a phenomenon in which an electric voltage arises due to the connection or contact of two electrodes connected to a solid or liquid system when receiving light energy. Therefore, solar cells are often referred to as photovoltaic (PV) cells. The Photovoltaic effect was discovered by Henri Becquerel in 1839. The purpose of a literature survey or literature review is to find out whether previous research has found an answer to our question. Hermawan (2009:42) suggests in his book that if the answers to our questions have been found in other research reports, then we must choose another topic or improve the results of existing research to make the topic more specific. There are several acceptable methods of citing references in the literature survey section and using citations. Publications Manual of the American Psychological Association (2001), The Chicago Manual of Style (1993), and Manual for Writers (1996) by Turabian. With this research, it is hoped that we can find out the development of electric cars and how much power electric cars are circulating in Indonesia and the use of solar energy to power electric cars circulating in Indonesia.